2016
DOI: 10.4103/0975-1475.195109
|View full text |Cite
|
Sign up to set email alerts
|

Lip outline: A new paradigm in forensic sciences

Abstract: Introduction:Personal identification is becoming increasingly important not only in legal medicine but also in crime/criminal investigation and identification. Sometimes establishing a person's identity can be a very difficult process. Dental, fingerprint, and DNA comparisons are probably the most common technique used. However, there are many well-known implanted methods of human identification, one of the most interesting emerging methods of human identification which originates from the criminal and forensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 4 publications
0
2
0
2
Order By: Relevance
“…Dentre os aspectos da unicidade, as impressões labiais são diferentes entre si, assim como diferentes entre os indivíduos, mesmo que estes sejam gêmeos (Suzuki & Tsuchiahashi, 1971;Molano et al 2002;Barros, 2006;Caldas et al, 2007;Sharma et al, 2009;El Domiaty et al, 2010;Costa & Caldas, 2012;Karki, 2012;Kumar et al, 2012;Oliveira et al, 2012;Padmavath et al, 2013;Ragab et al, 2013;Eldomiaty et al, 2014;Nagalaxmi et al, 2014;Hernández et al, 2015;Lima et al, 2016;Maloth et al, 2016;Moshfeghi et al, 2016;Saxena, et al, 2016;Kumar et al, 2017;Jain, Poojitha & Bhatia, 2018;Loganadan et al, 2019). É considerada imutável, pois pode ser observada que há reparação da forma original dos lábios após uma lesão (Prabhu, Dinkar, Prabhu & Rao, 2012).…”
Section: Discussionunclassified
See 1 more Smart Citation
“…Dentre os aspectos da unicidade, as impressões labiais são diferentes entre si, assim como diferentes entre os indivíduos, mesmo que estes sejam gêmeos (Suzuki & Tsuchiahashi, 1971;Molano et al 2002;Barros, 2006;Caldas et al, 2007;Sharma et al, 2009;El Domiaty et al, 2010;Costa & Caldas, 2012;Karki, 2012;Kumar et al, 2012;Oliveira et al, 2012;Padmavath et al, 2013;Ragab et al, 2013;Eldomiaty et al, 2014;Nagalaxmi et al, 2014;Hernández et al, 2015;Lima et al, 2016;Maloth et al, 2016;Moshfeghi et al, 2016;Saxena, et al, 2016;Kumar et al, 2017;Jain, Poojitha & Bhatia, 2018;Loganadan et al, 2019). É considerada imutável, pois pode ser observada que há reparação da forma original dos lábios após uma lesão (Prabhu, Dinkar, Prabhu & Rao, 2012).…”
Section: Discussionunclassified
“…A região geográfica dos estudos variou, sendo 3 estudos no Brasil (Barros, 2006;Oliveira, Rabello & Fernandes, 2012;Lima, Costa, da Silva, do Nascimento, de Moraes & de Souza Lucena, 2016) e os demais foram realizados no exterior, como, por exemplo: 10 estudos na Índia (Augustine, Barpande & Tupkari, 2008;Sharma, Saxena & Rathod, 2009;Kumar, Vezhavendhan & Vendhan, 2012;Padmavath, Makkad, Rajan & Kolli, 2013;Nagalaxmi, Ugrappa, Naga Jyothi, Maloth & Kodangal, 2014;Maloth et al, 2016;Alzapur et al, 2017;Chaudhari et al, 2017;Kumar, 2017;Jain et al, 2018), 1 no Egito (Ragab et al, 2013), 1 na Colômbia (Hernández, Pabón & Paredes, 2015), 1 em Portugal (Costa & Caldas, 2012), 1 no Reino Unido (Saxena, Kumar & Sharma, 2016), 1 no Irã (Moshfeghi, Beglou, Mortazavi & Bahrololumi, 2016), 2 na Arábia Saudita (El Domiaty, Al-Gaidi, Elayat, Safwat & Gathe, 2010;Eldomiaty, Anwar & Algaidi, 2014), 1 no Nepal (Karki, 2012), e 1 na Indonésia (Loganadan, Dardjan, Murniati, Oscandar, Melinda & Zakiawat, 2019).…”
Section: Fonte: Autoresunclassified
“…Another adjuvant tool employing lip prints in forensic investigations is lip outline patterns. Maloth et al have shown that lip outline patterns have the potential to be used for human identification since they are individually unique [ 146 ].…”
Section: Lip Printmentioning
confidence: 99%
“…Since ancient times, the presence of a person at the crime scene used to be predicted by the fingerprints found at the crime scene. [1][2][3][4][5][6][7] Collection of fingerprints became the prerequisite of any forensic investigation. The fingerprint powder will fix to the residues left by the finger and give rise to the distinctive patterns that help to identify an individual.…”
Section: Introduction "Existence Is Identity Consciousness Is Identif...mentioning
confidence: 99%